2018
DOI: 10.3390/molecules23010194
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Improves Liver Steatosis in Ovariectomized Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease, and is associated with the development of metabolic syndrome. Postmenopausal women with estrogen deficiency are at a higher risk of progression to NAFLD. Estrogen has a protective effect against the progression of the disease. Currently, there are no safe and effective treatments for these liver diseases in postmenopausal women. Honokiol (Ho), a bioactive natural product derived from Magnolia spp, has anti-inflammatory, anti-angiogenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Based on the current finding, OVX rats had high lipid peroxidation in the liver, an increase in MDA and NO levels, and a decrease in SOD and GSH‐PX. Such findings suggest that ovariectomy causes oxidative stress in the liver, thereby aligning with previous findings (Jeong et al, ; Li et al, ). Estrogen could decrease ROS levels by increasing the production of SOD and GSH‐PX (Oge, Sezer, Özgönül, Bayraktar, & Sözmen, ).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the current finding, OVX rats had high lipid peroxidation in the liver, an increase in MDA and NO levels, and a decrease in SOD and GSH‐PX. Such findings suggest that ovariectomy causes oxidative stress in the liver, thereby aligning with previous findings (Jeong et al, ; Li et al, ). Estrogen could decrease ROS levels by increasing the production of SOD and GSH‐PX (Oge, Sezer, Özgönül, Bayraktar, & Sözmen, ).…”
Section: Discussionsupporting
confidence: 92%
“…Thin-layer chromatography was performed using 0.25 mm silica gel plates (Merck). 1 H-(600 MHz) and 13 C-NMR (150 MHz) spectra were recorded on an AVANCE III System 600 MHz spectrometer (Bruker, Billerica, MA, U.S.A.) as solutions in CDCl 3 or DMSO-d 6 . High-resolution (HR) MS were obtained using JMS-700 (JEOL) with electron ionization or Thermo Scientific, Q Exactive HF-X Hybrid Quadrupole-Orbitrap Mass Spectrometer (Germering, Germany) using electrospray To an acetone solution (4 mL) of honokiol (140 mg, 0.52 mmol) was added Cs 2 CO 3 (0.51 g, 1.6 mmol), followed by cyclobutylmethyl bromide (72 µL, 0.63 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…7) Biphenolic natural neolignans isolated from the bark of Magnolia officinalis, such as honokiol, 4′-O-methylhonokiol, magnolol, and obovatol, have been used as traditional medicines for treating gastrointestinal disorders, anxiety, and allergy. Recent studies revealed that honokiol and its analogs have various biological activities, such as antiangiogenesis, 8,9) anticancer, 10) anti-inflammatory, 11) antibacterial, 12) osteoclast genesis-suppressing, 13) hepatoprotective, 14) and neuroprotective activities. 15) Honokiol and its derivatives were reported to target multiple signaling pathways, including the nuclear factor kappa light chain enhancer of activated B cells (NF-κB), 16) p53, 17) epidermal growth factor receptor (EGFR), 18) GPR55, 19) and phosphoinositide 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [14] found that JJ012 human chondrosarcoma cells lose their mitochondrial membrane potential when treated at 10 µM of honokiol, thus leading to apoptosis. Other studies have also shown that honokiol markedly disrupted the balance of Bax/Bcl-2 ratio [13,18,34,63,[94][95][96][97]. The increasing ratio of proapoptotic to antiapoptotic Bcl-2 family proteins (Bax/Bcl-2) will induce the release of cytochrome c and other apoptogenic proteins through the mitochondrial membrane to the cytosol, subsequently leading to the activation of caspase cascade and apoptosis [34].…”
Section: Dual Induction Of Apoptotic and Necrotic Cell Deathmentioning
confidence: 99%
“…Therefore, one of the important steps in cancer management is to control tumour cell metastasis, especially for early-stage cancer patients [153]. Various studies have reported that honokiol has the capability to suppress tumour metastasis in different types of cancer including breast cancer [40,148,154], non-small cell lung cancer [44,155] ovarian carcinoma cells [28], lung cancer [50], U251 human glioma, as well as U-87MG and T98G human glioblastoma cell [63,65,94], oral squamous cell carcinoma (OSCC) [26], bladder cancer cell [143], pancreatic cancer [58], renal cell carcinoma [156,157], and gastric cancer cells [113]. For instance, the percentage of invading urinary bladder cancer (UBC) cells was significantly reduced by 67% and 92% upon 2.4 µg/mL and 4.8 µg/mL of honokiol treatment, respectively [143].…”
Section: Suppression Of Migration Invasion and Angiogenesis Of Cancementioning
confidence: 99%